Extension Communicators: More Important Players In An Old Game - Ann E. Reisner; Robert G. Hays (Journal of Applied Communications, 1988)
This paper explores tentative ideas about the effects which extension communicators might have on the relationship between agri-business writers and writers and editors for farm magazines and newspaper farm departments. An open-ended questionnaire was sent to members of two professional agricultural journalist associations: Newspaper Farm Editors Association and the American Agricultural Editors Association. Responses identified advertising and public relations writers as the principal perceived source of ethical dilemmas in agricultural journalism. None identified extension communicators as a source of concern. We suggest that the availability of extension news acts as a buffer for agricultural newspaper and magazine writers, protecting them from relying more heavily on agribusiness news copy.